A multicenter randomized controlled trial of medium‐chain triglyceride dietary supplementation on epilepsy in dogs. (15th April 2020) - Berk, Benjamin A.; Law, Tsz H.; Packer, Rowena M. A.; Wessmann, Annette; Bathen‐Nöthen, Andrea; Jokinen, Tarja S.; Knebel, Anna; Tipold, Andrea; Pelligand, Ludovic; Meads, Zoe; Volk, Holger A.
Abstract: Background: Medium‐chain triglyceride (MCT) enriched diet has a positive effect on seizure control and behavior in some dogs with idiopathic epilepsy (IE). Objective: To evaluate the short‐term efficacy of MCTs administered as an add‐on dietary supplement (DS) to a variable base diet to assess seizure control and antiseizure drug's (ASD) adverse effect profiles. Animals: Twenty‐eight dogs with International Veterinary Epilepsy Task Force Tier II (IVETF) level diagnosis of treated IE with 3 or more seizures in the last 3 months were used. Methods: A 6‐month multicenter, prospective, randomized, double‐blinded, placebo‐controlled crossover trial was completed, comparing an MCT‐DS with a control‐DS. A 9% metabolic energy‐based amount of MCT or control oil was supplemented to the dogs' diet for 3 months, followed by a control oil or MCT for another 3 months, respectively. Dogs enrolled in this study satisfied most requirements of IE diagnosis stated by the IVETF II level. If they received an oil DS or drugs that could influence the metabolism of the investigated DS or chronic ASD, the chronic ASD medication was adjusted, or other causes of epilepsy were found, the dogs were excluded from the study. Results: Seizure frequency (median 2.51/month [0‐6.67] versus 2.67/month [0‐10.45]; P = .02) and seizure‐day frequency were significantly (1.68/month [0‐5.60] versus 1.99/month [0‐7.42], P = .01) lower when dogs were fed MCT‐DS in comparison with the control‐DS. Two dogs were free of seizures, 3 had ≥50% and 12 had <50% reductions in seizure frequency, and 11 dogs showed no change or an increase in seizure frequency. Conclusions and Clinical Importance: These data show antiseizure properties of an MCT‐DS compared to a control oil and support former evidence for the efficacy of MCTs as a nutritive, management option for a subpopulation of drug‐resistant dogs with epilepsy.